BIOREDUCTION AND CHARACTERIZATION OF SILVER NANOPARTICLES FROM OIL PALM EMPTY FRUIT BUNCH - Siti Suhartati; Iwan Syahjoko Saputra; Dwinna Rahmi; Yoki Yulizar; Sudirman Sudirman (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2020)
BIOREDUCTION AND CHARACTERIZATION OF SILVER NANOPARTICLES FROM OIL PALM EMPTY FRUIT BUNCH (OPEFB). The synthesis of silver nanoparticles was successfully carried out by extracting oil palm empty fruit bunch. The precursor used was silver nitrate (AgNO3) with a concentration of 9x10-4 M and 5 wt% of the oil palm empty fruit bunch extract. OPEFB acted as a capping agent in the synthesis of silver nanoparticles. The bioreduction method Ag+ to Ag0 produced a silver nanoparticle colloid in brown color. The results of the UV-Vis spectrophotometer showed the silver nanoparticles colloids spectrum at a wavelength of 420 nm with an absorbance value of 0.5. FTIR shows the reduction and shift of absorption peak in the hydroxyl functional group (-OH) at wavenumbers of 3323 cm-1 and the presence of absorption peaks at 560 cm-1. While, XRD pattern showed the specific crystallinity peaks of silver nanoparticles at 2θ: 33.24°; 39.98°; 61.23°; dan 79.13° respectively with the face-centered cubic crystal structure (FCC) and crystallite size of 15 nm. PSA analysis showed two specific peaks with an average size distribution silver nanoparticles of 43.5 nm and a PDI value of 0.4. Analysis of TEM shows the average particle size of 20 nm with a spherical particle shape.